Surface modification to improve biointegration of materials in a core-skirt keratoprosthesis - Riau, Andri Kartasasmita (2017)
Corneal disease is a major leading cause of blindness worldwide. The majority of the reversible causes could benefit from corneal transplantation. However, transplantation-grade donor corneas are often difficult to procure. In addition, organ transplantation is frequently plagued by clinical, ethical and logistical issues. Prognosis of corneal transplantation is also poor in most advanced corneal diseases. In these cases, implantation of an artificial cornea becomes the next viable option. Core-skirt keratoprosthesis (KPro) is a type of artificial cornea and the most widely used ocular prosthetic device. This KPro construct consists of a transparent optical core which is usually made of a polymer, such as poly(methyl methacrylate) (PMMA), surrounded by a skirt material which is usually a biological material that promotes biointegration, such as the donor corneal tissue. Various studies in the literature have highlighted a common problem associated with core-skirt KPros, which is the poor interfacial bonding and biointegration between the two materials (PMMA and biological material). Surface modification is an attractive technique that can be employed to improve the interactions and bonding strength between the two dissimilar materials without significantly altering the design of the KPro. The main objective of this thesis, therefore, was to apply surface modification on PMMA to enhance its interactions and adhesion to the skirt material. Collagen type I hydrogel was selected as the substitute skirt material to eliminate the use of human donor corneas. A novel dip coating method, which was simple and inexpensive to execute for immobilizing HAp nanoparticles on PMMA was introduced in this thesis to address problems associated with conventional HAp coating method. One time dip in 20% (w/v) HAp nanoparticles in 5% (w/v) PMMA/chloroform for 60 seconds, followed by surface plasma irradiation (referred to as HAp-coated PMMA) resulted in a homogenous coating on PMMA sheets, offering high hydrophilicity, resistance to delamination and preservation of Ca/P ratio of pure HAp. These advantages resulted in 2.5 times improvement in adhesion strength (over 28 days in artificial tear fluid) between collagen hydrogel and HAp-coated PMMA than between hydrogel and d-CaP (apatite coating via simulated body fluid incubation), and an order of magnitude improvement compared to untreated PMMA. Corneal stromal fibroblasts were able to form good adhesion and proliferate on the HAp-coated PMMA. The dip coating technique could be extended to immobilize HAp nanoparticles on PMMA cylinders, bringing the studies closer to the clinical application of the coating for KPro optical cylinders. However, minor modification in the dip coating method (12 times 5-second-dips instead of 1 time 60-second-dip) was necessary to immobilize the nanoparticles on PMMA cylinders of 3 mm in diameter due to the curved surface and smaller surface area compared to PMMA sheets. An advantage of substituting donor cornea with collagen hydrogel as the skirt material was also presented in this thesis, whereby an antibiotic (vancomycin) was loaded in the hydrogel (referred to as VH) and was shown to be bactericidal effective in vitro for up to 7 days. When implanted in the rabbit corneas, which were infected with Staphylococcus aureus, the VH-implanted corneas were clear and non-edematous and showed a reduction of log 2.5 in bacteria compared to the blank hydrogel-implanted corneas.